Neither - Basciano, Oliver; Brenner, Fernanda (Berlin : Bom dia boa tarde boa noite, 2019)
Costa, Adriano ; Mackie, Christina ; Panayiotou, Christodoulos ; Cavalli Bastos, Cibelle ; João Scavarda, Francesco ; Coopey, Dan ; Verzutti, Erika ; f.marquespenteado ; Steegmann Mangrané, Daniel ; Roque, Luiz ; Algün, Meriç ; Dean, Michael ; Deshayes, Nicolas ; Dodge, Jason ; Canell, Nina ; Castillo Deball, Mariana ; Bosquê, Paloma ; Leite, Patricia ; Arruda, Lucas ; Lagomarsino, Runo ; Gomes, Sonia ; Halloubi, Hamza
Neither, Mendes Wood DM, Brussels, 18 April - 17 June 2017
boek